2020
DOI: 10.3390/w12102904
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pressure and Nozzle Size on the Spray Characteristics of Low-Pressure Rotating Sprinklers

Abstract: Using low-pressure sprinklers in agricultural irrigation has become an alternative way of reducing water and energy stress. To determine the applicability of the low-pressure rotating sprinkler, an experiment was conducted to evaluate the effects of working pressure and nozzle size on sprinkler rotation speed, application rate, droplet size, droplet velocity, droplet trajectory angle, and kinetic energy distribution. The results showed that the mean droplet diameter increased exponentially along with the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Fixed spray plate sprinklers (FSPSs), rotating spray plate sprinklers (RSPSs) and oscillating spray plate sprinklers (OSPSs) can be classified as low‐pressure sprinklers with specific designs and operating conditions (Manke et al, 2019). Numerous studies have shown that RSPSs have higher energy consumption in addition to having a wide spraying range, low wind drift, evaporative losses and a relatively uniform distribution of water (Chen et al, 2020; Faci et al, 2001; Hills & Barragan, 1998). The cost of an FSPS was lower than that of an RSPS, but this sprinkler type attained high instantaneous application rates and poor application uniformity, which caused soil and water loss (Silva, 2007; Yan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fixed spray plate sprinklers (FSPSs), rotating spray plate sprinklers (RSPSs) and oscillating spray plate sprinklers (OSPSs) can be classified as low‐pressure sprinklers with specific designs and operating conditions (Manke et al, 2019). Numerous studies have shown that RSPSs have higher energy consumption in addition to having a wide spraying range, low wind drift, evaporative losses and a relatively uniform distribution of water (Chen et al, 2020; Faci et al, 2001; Hills & Barragan, 1998). The cost of an FSPS was lower than that of an RSPS, but this sprinkler type attained high instantaneous application rates and poor application uniformity, which caused soil and water loss (Silva, 2007; Yan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the rapid decrease of AR led to the decrease of the SP value. According to the general situation, the peak value of SP appears only when the droplet diameter, velocity, and AR remain at a high level [15]. However, due to the special structure of the Nelson R33 sprinkler used in this study, the device used to aggravate the droplet breakage was added, which significantly reduced the impact of working pressure on the droplet characteristics.…”
Section: Radial Kinetic Energymentioning
confidence: 94%
“…Issaka et al [14] studied the effects of different forms of diffusers on jet breaking through the combination of high-speed photography experiments and computational fluid dynamics simulations to obtain better structural parameters. Chen et al [15] determined the spray characteristics of a low-pressure rotating non-circular sprinkler with a diffuser. However, commercially available low-pressure rotating sprinklers with diffusers are scare.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Sprinkler irrigation technology, a relatively modern irrigation method used by farmers to improve irrigation efficiency, water and fertilizer use, and crop yield and quality, has been widely promoted and applied worldwide. [2] However, sprinkler irrigation also plays an important role on irrigation-based erosion. [3,4] Energy-carrying water droplets produced by sprinkler irrigation systems can essentially describe the critical mechanism of DOI: 10.1002/clen.202100280 soil particle transport.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Sprinkler irrigation technology, a relatively modern irrigation method used by farmers to improve irrigation efficiency, water and fertilizer use, and crop yield and quality, has been widely promoted and applied worldwide. [ 2 ] However, sprinkler irrigation also plays an important role on irrigation‐based erosion. [ 3,4 ]…”
Section: Introductionmentioning
confidence: 99%